How to manage your kindergarten classroom - Thomas, Rosalind (Huntington Beach, Calif. Teacher Created Materials, Inc., 1995)
Contains information, activities, and examples for the kindergarten classroom teacher.
Keywords: Classroom management; Kindergarten teachers; Kindergarten -- Handbooks, manuals, etc